Liquidity forecasting at corporate and subsidiary levels using machine learning - Vinay Singh; Bhasker Choubey; Stephan Sauer (Intelligent Systems in Accounting, Finance and Management, 2024)
Liquidity planning and forecasting are essential activities in corporate financial planning team. Traditionally, empirical models and techniques based on in-house expertise have been used to navigate the numerous challenges of this forecasting activity. These challenges become more complex when the forecasting activities are extended to subsidiaries of a large firm. This paper presents a structured approach that utilizes 240 covariates to predict net liquidity, customer receipts, and payments to suppliers to improve the accuracy and efficiency of liquidity forecasting in subsidiaries and at the corporate level. The approach is empirically validated on a large corporation headquartered in Germany, with average annual revenue from 6 to 7 billion Euro spanning 80 countries. The proposed approach demonstrated superior performance over existing methods in six out of nine forecasts using the data from 2014 to 2018. These findings suggest that a firm's classical approach to liquidity forecasting can be effectively challenged and outperformed by the algorithmic approach.
Keywords: 650; corporate finance planning; forecast; liquidity planning; machine learning algorithms